Impact Influence Providing Health Education Using Storytelling Method to the Level of Knowledge Dental Hygiene in Children Age School - Mukriani, Mukriani (International Journal of Health Sciences, 2025)
Dental health is one of aspect important in grow flower children. However, understanding child age school about importance cleanliness tooth Still classified as low. Appropriate educational efforts with stage development children are very much needed for knowledge can absorbed optimally. The storytelling method is approach effective educational​ for child age school Because blend element education and entertainment. Research This aiming for know impact influence giving education health use method tell a story to improvement knowledge cleanliness teeth in children age school. Research This use pre- experimental design with one group pre-test and post-test approach. Subject study is student grades III and IV of elementary school in the X City area, as many as 60 respondents. The results of the study show existence improvement significant at the level knowledge after given intervention in the form of story educative about health teeth. Storytelling method proven effective increase understanding child in guard cleanliness tooth in a way independent. Implications from study This is importance integration approach creative and fun in education health child.